Islet cell xenotransplantation: a serious look toward the clinic. (8th May 2014) - Samy, Kannan P.; Martin, Benjamin M.; Turgeon, Nicole A.; Kirk, Allan D.
Abstract Type I diabetes remains a significant clinical problem in need of a reliable, generally applicable solution. Both whole organ pancreas and islet allotransplantation have been shown to grant patients insulin independence, but organ availability has restricted these procedures to an exceptionally small subset of the diabetic population. Porcine islet xenotransplantation has been pursued as a potential means of overcoming the limits of allotransplantation, and several preclinical studies have achieved near‐physiologic function and year‐long survival in clinically relevant pig‐to‐primate model systems. These proof‐of‐concept studies have suggested that xenogeneic islets may be poised for use in clinical trials. In this review, we examine recent progress in islet xenotransplantation, with a critical eye toward the gaps between the current state of the art and the state required for appropriate clinical investigation.